Media Sosial, Literasi Digital, Dan Inovasi Bisnis Trikotomi Baru Dalam Manajemen Strategi - Yunita Wono, Hilda; Novaldo, Novldo; Fitriani, Fitriani (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2023)
This research aims to explore the impact of digital literacy, utilization of social media, and business innovation on company growth strategies. The researcher employed a qualitative research methodology, involving the analysis of company reports, in-depth interviews with senior managers and executives, as well as content analysis. The research findings indicate that a high level of digital literacy within the organization plays a pivotal role in supporting the company's ability to adopt cutting-edge technology and formulate innovative strategies that are responsive to market changes. Furthermore, effective use of social media intensifies the relationship between the company and its customers, enhances brand awareness, and has a positive impact on strategic decision-making. On the other hand, business innovation driven by advances in digital technology provides a greater competitive advantage in facing the rapid dynamics of the market. In connection with this, the results of this study offer valuable guidance for business practitioners, emphasizing the significance of investing in digital literacy, developing shrewd social media strategies, and fostering a strong culture of innovation as key elements in company strategic management in the digital era.